Carnivalesque Reversal and Liminal Escape in Deudākhel (Sudurpaschim Spectrum, 2024)
The purpose of this article is to investigate the interconnection between performer, performance and audience during the performance procession of deudākel. The paper, however, illustrates how dynamic interplay of spiral steps along with antiphonal singing foregrounds celebration of equality, freedom and abundance to enjoy performative transference during deudākhel. The ritual canons and performance dynamic of deudākhel, implicitly, comprises carnivalesque resemblances, which contradict with everyday rustic life. Looking through Bakhtin’s concepts of carnivalesque and Turner’s critical outlook of liminality and communitas, this article seeks to examine how spatial and temporal interruption in the performance transforms, temporarily, the prevailing normative social order with special reference to deudākhel. Literature surrounding the carnivalesque and liminality refers to the subversion of hierarchies and social status. Thus, the paper interlinks sets of ideas that deudākhel consolidates to carnivalesque, liminality and communitas in framing ritual dynamic of slanted steps and chanting poetic refrains of deudākhel. The folksong deudā has basically two ritual dimensions-solo chanting and group performance. This paper argues that festive celebration of deudākhel is temporary transgression from mundane of everyday folk life; disrupts the established flow; and celebrates freedom, equality and abundance. This article concludes that the kinesthetic spiral movement of chanting/ singing during the performance procession of deudākhel suspends rustic everyday drudgery by forming liminal communitas of transitional order.